The adoption of Global Sourcing by a Brazilian Company - Nunes, Moema Pereira (2013)
Companies are going abroad looking for advantages from alternative sources of supply. Primarily associated with the lack of local supplier or lower acquisitions costs, these reactive reasons have driven business to a more proactive perspective by the adoption of a Global Sourcing (GS). Companies from emerging countries are developing their own GS, just like multinational from developed countries. These "late movers" have a strategic motivation, and goals, to internationalize their activities. This paper reviews and integrates literature from Operations Management, Strategic Management and International Business areas to develop a framework that poses 13 theoretical propositions. Then, the paper presents a case study carry out in a Brazilian electro- electronics company that develops and manufactures its products overseas and distributes them in Brazil and other South American markets. This company replicates the strategy developed in its home country and spread value chain activities through global suppliers, especially those located in Asia. Findings reveal that the company has the capability to analyze its value chain to focus on the activities that add more value: those are product development and distribution in South America. Each proposition of the framework was illustrated by the empirical evidence from the case study. The findings provide insights to guide further research on the adoption of GS by companies from emerging countries. Some propositions of the theoretical framework were not found due to the size and strategy of the analyzed company and new propositions were developed based on the empirical findings for further research.DOI: 10.12660/joscmv6n2p114-127URL: http://dx.doi.org/10.12660/joscmv6n2p114-127